Evaluation of Spatial/3D Audio: Basic Audio Quality Versus Quality of Experience - Schöffler, Michael; Silzle, Andreas; Herre, Jürgen (IEEE Journal of Selected Topics in Signal Processing, 2017)
During the past decades, spatial reproduction of audio signals has evolved from simple two-channel stereo to surround sound (e.g., 5.1 or 7.1) and, more recently, to three-dimensional (3D) sound including height speakers, such as 9.1 or 22.2. With increasing number of speakers, increasing spatial fidelity and listener envelopment are expected. This paper reviews popular methods for subjective assessment of audio. Moreover, it provides an experimental evaluation of the subjective quality provided by these formats, contrasting the well-known basic audio quality (BAQ) type of evaluation with the more recent evaluation of overall listening experience (OLE). Commonalities and differences in findings between both assessment approaches are discussed. The results of the evaluation indicate that 3D audio enhances BAQ as well as OLE over both stereo and surround sound. Furthermore, the BAQ- and OLE-based assessments turned out to deliver consistent and reliable results.
herre_books_journals
Keywords: 3D audio; basic audio quality; overall listening experience; Subjective assessment